Task-specific brain reorganization in motor recovery induced by a hybrid-rehabilitation combining training with brain stimulation after stroke. (March 2015) - Koganemaru, Satoko; Sawamoto, Nobukatsu; Aso, Toshihiko; Sagara, Akiko; Ikkaku, Tomoko; Shimada, Kenji; Kanematsu, Madoka; Takahashi, Ryosuke; Domen, Kazuhisa; Fukuyama, Hidenao; Mima, Tatsuya
Highlights: We developed a new hybrid-rehabilitation combining rTMS and motor training for stroke. We investigated the task-specific multi-regional brain reorganization induced by it. We found reduced activities in ipsilesional SMC, contralesional CMC and PMC after it. The findings were shown only for the trained movements but not for the untrained ones. The clinical improvements were associated with the amount of activation change. Abstract: Recently, we have developed a new hybrid-rehabilitation combining 5 Hz repetitive transcranial magnetic stimulation and extensor motor training of the paretic upper-limb for stroke patients with flexor hypertonia. We previously showed that the extensor-specific plastic change in M1 was associated with beneficial effects of our protocol (Koganemaru et al., 2010 ). Here, we investigated whether extensor-specific multiregional brain reorganization occurred after the hybrid-rehabilitation using functional magnetic resonance imaging. Eleven chronic stroke patients were scanned while performing upper-limb extensor movements. Untrained flexor movements were used as a control condition. The scanning and clinical assessments were done before, immediately and 2 weeks after the hybrid-rehabilitation. As a result, during the trained extensor movements, the imaging analysis showed a significant reduction of brain activity in the ipsilesional sensorimotor cortex, the contralesional cingulate motor cortex and the contralesional premotor cortex in association with functional improvements of the paretic hands. The activation change was not found for the control condition. Our results suggested that use-dependent plasticity induced by repetitive motor training with brain stimulation might be related to task-specific multi-regional brain reorganization. It provides a key to understand why repetitive training of the target action is one of the most powerful rehabilitation strategies to help patients.